Intradialytic Parenteral Nutrition in Pediatrics - Juarez, Marisa Danielle (Frontiers in Pediatrics, 2018)
Pediatric end stage renal disease (ESRD) patients on hemodialysis are at increased risk for malnutrition. Aggressive nutrition intervention such as intradialytic parenteral nutrition (IDPN) should be considered to prevent further co-morbidities and mortality associated with malnutrition when other interventions fail. IDPN is a non-invasive method of providing nutrition to malnourished hemodialysis (HD) patients via the HD access throughout the treatment. Although the evidence on the long-term benefits of IDPN is scant in pediatrics, there is evidence that it improves nutritional status and metabolic parameters. The aim of the present paper is to define IDPN, present a protocol to initiating the therapy as well as goals and elements to monitor while on IDPN. A guide for practitioners to prescribe IDPN is also presented.